Oncologic outcomes of preoperative stent insertion first versus immediate surgery for obstructing left-sided colorectal cancer. (June 2018) - Kang, Sung Il; Oh, Heung-Kwon; Yoo, Jae Suk; Ahn, Soyeon; Kim, Min Hyun; Kim, Myung Jo; Son, Il Tae; Kim, Duck-Woo; Kang, Sung-Bum; Park, Young Soo; Yoon, Chang Jin; Shin, Rumi; et al.
Abstract: Background: Colonic self-expanding metallic stenting (SEMS) is widely used for the treatment of malignant colonic obstruction as a bridge to elective surgery. However, the effects of colonic stenting on long-term oncologic outcomes are debatable. This study aimed to compare the long-term oncologic outcomes of preoperative SEMS insertion with those of immediate surgery in patients with obstructing left-sided colorectal cancer. Methods: A cohort of consecutive patients who underwent radical surgery for obstructing left-sided colorectal cancer between 2004 and 2011 in five tertiary referral hospitals were analyzed. Long-term survivals were analyzed and adjusted using the inverse probability of treatment weighting method, based on propensity scores, to reduce selection bias. Results: One hundred and nine patients underwent immediate surgery, and 226 underwent stent insertion before surgery. Disease-free survival did not differ significantly in both the unadjusted population (hazard ratio [HR] 1.063, 95% confidence interval [CI] 0.730–1.548; Log-rank, p = 0.746) and the adjusted population (HR 0.122, 95% CI 0.920–1.987; Log-rank, p = 0.122). Overall survival also did not differ significantly in both the unadjusted population (HR 0.871, 95% CI 0.568–1.334; Log-rank, p = 0.526) and the adjusted population (HR 1.023, 95% CI 0.665–1.572; Log-rank, p = 0.916). Defunctioning stoma formation was less in the SEMS insertion group than immediate surgery group (adjusted, 14.6% vs. 41.3%, p < 0.001). Conclusion: The 'bridge to surgery' strategy using metallic stents was oncologically comparable to immediate surgery in patients with malignant left-sided colorectal obstruction. Highlights: Disease-free survival rate was comparable, SEMS insertion vs. immediate surgery. Overall survival rate was comparable between the two groups. Defunctioning stoma formation was less in the SEMS insertion group. The 'bridge to surgery' strategy using stent insertion was oncologically acceptable.